Dante’s Legacy: Kinship between Languages in Seamus Heaney’s Poetics - Daniela Panzera (Estudios Irlandeses, 2016)
Dante’s influence on Seamus Heaney’s poetry – generally analyzed from a religious, philosophical, and cultural perspective – has been widely acknowledged by critics and by Heaney himself. Heaney, though, was also fascinated with Dante’s stylistic achievements and concern for themes such as land, politics and language. As a conscious innovator of his time, Dante developed the vernacular in literature, demonstrating that it was suitable for poetic expression. He created a universal idiom out of the various Italian dialects, believing that a common tongue was the means to achieve some form of national unity. Following Dante’s example, in the place-name poems “Broagh” and “Anahorish” (Wintering Out), Heaney reunites both the English and the Irish traditions through a meditation of the semantic elements of both cultures. Moreover, in his collection Electric Light, and in his translation of Dante’s “Ugolino” (Inferno XXXII-XXXIII), the Irish poet places the local aspects of his culture in a universal framework. This article will display how, through his engagement with Dante and through the specific practice of translation, Heaney is able to transcend ethnic boundaries in order to obtain an objective view of the world. Like his medieval predecessor, in his works Heaney locates the global in the local and vice versa, emphasizing the epistemological value of constructively interacting with other cultures and languages, which ultimately enriches an understanding of one’s own cultural identity.